2006
DOI: 10.1007/s10336-006-0074-4
|View full text |Cite
|
Sign up to set email alerts
|

Parental food conditions affect sex-specific embryo mortality in the yellow-legged gull (Larus michahellis)

Abstract: Different mortality of males and females during early post-hatching development in sexually size-dimorphic bird species is usually attributed to different nutritional requirements of the sexes, because mortality is mostly biassed toward the larger sex. We investigated whether sex-specific embryo mortality in the yellow-legged gull (Larus michahellis), a sizedimorphic seabird, depends on parental condition. To test this, we experimentally modified parental nutritional conditions by supplementary feeding of yell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 64 publications
1
20
0
Order By: Relevance
“…The pairs in the control group were fed in a similar manner but without fuel oil and only with sunflower oil (for more details about food supplementation, see Pérez et al 2006Pérez et al , 2008b.…”
Section: Methodsmentioning
confidence: 99%
“…The pairs in the control group were fed in a similar manner but without fuel oil and only with sunflower oil (for more details about food supplementation, see Pérez et al 2006Pérez et al , 2008b.…”
Section: Methodsmentioning
confidence: 99%
“…Yellow-legged gulls are territorial, defending aggressively several meters around their nest site (AlonsoAlvarez, 2001; Alonso-Alvarez and Velando, 2001). Moreover, a previous experience providing food in the same way and registering behavior of gulls around the territory reported that no food item was stolen by other birds (Pérez et al, 2006). The other 19 pairs (control birds, "C-birds") were fed in the same way, but the bread did not contain fuel oil, but only vegetable oil.…”
Section: Methodsmentioning
confidence: 99%
“…Rutkowska and Cichoń 2002;Bogdanova et al 2007). Furthermore, previous studies have shown that male and female embryo survival is differentially affected by conditions during embryonic development (Göth and Booth 2005;Pérez et al 2006), and unfavourable pre-natal developmental conditions can have long-lasting sex-specific effects on future performance (Gorman and Nager 2004).…”
Section: Introductionmentioning
confidence: 99%